The measurement and dimensionality of e-learning blog satisfaction: Two-stage development and validation. Issue 5 (30th September 2014) - Wang, Yi-Shun; Li, Ci-Rong; Lin, Hsin-Hui; Shih, Ying-Wei
Abstract : Purpose: – The purpose of this paper is to develop and validate a multi-dimensional instrument to measure e-learning blog satisfaction (ELBS). Design/methodology/approach: – This study introduces and defines the construct of ELBS, provides an empirical validation of the construct and its underlying dimensionality, develops a generic ELBS instrument with desirable psychometric properties, and investigates the instrument's theoretical and practical applications. Findings: – After analyzing data from a calibration sample ( n =238) and a validation sample ( n =226), this study proposes a five-factor, 20-item ELBS instrument. Practical implications: – This empirically validated instrument will be useful to researchers in terms of developing and testing blog-based learning theories, as well as to educators in terms of understanding students' ELBS and promoting the use of blog-based learning systems. Originality/value: – This study is a pioneering effort to develop and validate a multi-dimensional instrument to measure ELBS.